Intention to donate money via social network site : perspective from a developing country - Tze, Kiat Lui; Mohd Haniff Zainuldin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Charity fundraising is challenging, yet the social network site (SNS) has changed the way to drive money donations. The largest SNS user group in Malaysia is comprised of university students. However, they are the least contributed group in making donations. This study examines the factors influencing the intentions of students to donate money via SNS. A cross-sectional online survey was conducted, and the data from 216 questionnaires were analysed using multiple linear regression. Using the extended theory of planned behaviour, three constructs, namely, descriptive norm, perceived behavioural control, and Internet technology feature, were found to significantly affecting the intention for online donations. Normalising the majority’s performance in a similar reference group and making students feel comfortable sharing their online giving information have positive effects on donation intention via SNS. The young people were also concerned about the Internet functionality to perform monetary donation over SNS. The other two constructs that are, attitude and past behaviour, were not significant towards intention to donate via SNS. The findings offered several suggestions to non-profit organisations to raise the awareness of online giving among students, as to shape them to become future donors for far-reaching decades.